The Book of Job. Aesthetics, Ethics, Hermeneutics - Batnitzky, Leora (Perspectives on Jewish Texts and Contexts, 2015)
The Book of Job has held a central role in defining the project of modernity from the age of Enlightenment until today. Why has Job`s response to disaster become a touchstone for modern reflections on catastrophic events? This volume engages this question and offers new perspectives on the tragic bent of the Book of Job, on its dramatic irony, on Job`s position as mourner, and the unique representation of the Joban body in pain.